2010
DOI: 10.3109/09537104.2010.501119
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and its thiolactone may promote apoptotic events in blood plateletsin vitro

Abstract: The actions of homocysteine and its major metabolite, cyclic thioester, homocysteine thiolactone on endothelial cells, blood platelets, plasmatic fibrinogen and plasminogen--the important major components of haemostasis, regulating the flowing properties of blood--are complex and sometimes controversial. Homocysteine (Hcys) can promote apoptosis in endothelial cells, but the role of Hcys and its thiolactone in the apoptotic process in blood platelets is unknown. In order to study the appearance of apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…Неблагоприятные эффекты гомоцистеина при метаболических нарушениях опосредуются через различные факторы гиперкоагуляции [5,22]. Данные мировой литературы указывают на значительное увеличение уровня фибриногена, числа тромбоцитов и высвобождаемых ими прокоагулянтных микрочастиц в ответ на введение гомоцистеина [23][24][25][26], однако результаты исследований в отношении показателей тромбодинамики при ГГЦ спорны. По данным R. Marchi и соавт., уровень гомоцистеина в крови не оказывает значимого влияния на показатели тромбодинамики [27].…”
Section: Discussionunclassified
“…Неблагоприятные эффекты гомоцистеина при метаболических нарушениях опосредуются через различные факторы гиперкоагуляции [5,22]. Данные мировой литературы указывают на значительное увеличение уровня фибриногена, числа тромбоцитов и высвобождаемых ими прокоагулянтных микрочастиц в ответ на введение гомоцистеина [23][24][25][26], однако результаты исследований в отношении показателей тромбодинамики при ГГЦ спорны. По данным R. Marchi и соавт., уровень гомоцистеина в крови не оказывает значимого влияния на показатели тромбодинамики [27].…”
Section: Discussionunclassified
“…104 Others showed that homocysteine rather leads to apoptosis of human platelets as it dose-dependently increased phosphatidyl serine exposure, microparticle formation, mitochondrial membrane depolarization, and caspase activation. 143,144 Indoles and Derivates Indoxyl sulfate, a tryptophan metabolite, has prothrombotic properties. It enhanced platelet reactivity toward collagen stimuli via p38-MAPK signaling in mouse platelets.…”
Section: Protein-bound Compounds Advanced Glycation End Products and ...mentioning
confidence: 99%
“…104 Others showed that homocysteine rather leads to apoptosis of human platelets as it dose-dependently increased phosphatidyl serine exposure, microparticle formation, mitochondrial membrane depolarization, and caspase activation. 143,144…”
Section: Uremic Toxin-induced Platelet Abnormalitiesmentioning
confidence: 99%